Oxidation resistance and mechanical characterization of silicide coatings on the Nb-18Ti-14Si-9Al alloy. (December 2017) - Sun, Zhiping; Tian, Xiaodong; Guo, Xiping; Yin, Mengjiao; Zhang, Fengying; Zhang, Xuemin
Abstract: The Nb-Si alloys are attractive candidate for more advanced aircraft engines, however their oxidation resistances are poor. In this work, silicide coatings were prepared on the Nb-18Ti-14Si-9Al substrate, and we present the concern of this Nb-Si alloy with high Al content, and focused the modification effect of Al on NbSi2 coatings. It is found that composition of the substrate alloy have an essential effect on coatings, which is composed of (Nb, Ti)Si2 outer layer and (Nb, Ti)Si2  + (Nb, Ti)3 Si5 Al2 inner layer. Underneath inner layer, NbAl3 is formed and surrounded by Nb5 Si3 . Beyond fracture toughness test, the coating still preserved the integrity and tightly adhered to substrate, no cracks nucleated between substrate and the coating. After oxidation at 1250 °C for 50 h, the mass gain of substrate and silicide coating is 398.85 mg/cm 2 and 2.34 mg/cm 2 respectively. The excellent oxidation resistance of the coating is proved to benefit from modification effects of high Al in the substrate. Highlights: The silicide coatings for the Nb-Ti-Si-Al alloy were developed and characterized. Al in substrate beneficially modified the structure and properties of the coating. The coatings were composed of major (Nb, Ti)Si2 and some (Nb, Ti)3 Si5 Al2 . After fracture, the coating preserved integrity and tightly adhered to substrate. Coated alloys possessed much better oxidation resistance than uncoated alloys.